Preliminary QTL detection for Corynespora Leaf Fall disease resistance in rubber plant - Fetrina Oktavia; Sudarsono SUDARSONO; Diny Dinarti (Nusantara Bioscience, 2021)
Abstract. Oktavia F, Sudarsono, Dinarti D. 2021. Preliminary QTL detection for Corynespora Leaf Fall disease resistance in rubber plant. Nusantara Bioscience 13: 53-61. Corynespora Leaf Fall (CLF) disease caused by Corynespora cassiicola fungus is one of the most important diseases of rubber trees. Conventional breeding to obtain the resistant rubber clones was constrained by the long time required for selection processes. This study was aimed to identify resistant loci linked with CLF disease on the rubber tree. Analysis was conducted on 104 F1 of BPM 1 x RRIM 600. The resistance evaluation of the population had been done against two C. cassiicola isolates and the molecular analysis was generated by using 28 selected SSR markers. There was a phenotypic variation in F1 resistance to both isolates with leaf wilting intensities ranged from 5.2% to 33.4% on CC-06 isolate, and from 3.5% to 36.4% on CC-22 isolate. There was no QTL identified on the genetic linkage map, but a single marker analysis showed that some loci associated with CLF disease. The associated loci can be used as a preliminary information to develop molecular markers linked with resistance to CLF disease to assist the rubber breeding programs.